Checklist of Myxomycetes (Amoebozoa) of the Polish Tatra Mts - Wojciech Paul; Paulina Janik; Anna Ronikier (Acta Mycologica, 2024)
The Tatra Mts are the highest mountain range in the Carpathians and are an important biodiversity region for many organisms. Plants, animals, and fungi are better studied in this region, while myxomycetes still remain understudied. This study presents the most up-to-date checklist of myxomycetes in the Polish Tatra Mts. The list is based on the published literature data and new records from the years 2000-2019. Overall, 85 species are reported, four are new to Poland ( Arcyria cf. helvetica , Cribraria macrospora , Fuligo cf. licentii , and Nannengaella cf. mellea ), and 30 taxa (species or varieties) are reported for the first time from the study area.